FACTORS IN THE FORMATION OF PROSTATE CANCER - Умуров Бобиржон Файзиллоевич (Web of Journals Publishing, 2024)
Prostate cancer is one of the most common forms of malignant tumors among men, and its development is associated with a variety of factors, including genetic, hormonal, environmental, and lifestyle-associated risks. The article discusses the main factors contributing to the occurrence of prostate cancer, such as age, family history, ethnicity, as well as the influence of diet and environment hormones and gene mutations associated with tumor progression. In addition, modern approaches to prevention and diagnosis that can help reduce morbidity and improve prognosis for patients are analyzed.
Keywords: Prostate cancer, risk factors, genetic mutations, hormone therapy, diet, ecology, prevention, diagnostics, androgenic hormones.